Transformation of Chinese media language under the influence of digital environment - Yi, Ren (Journal of the Belarusian State University. Philology, 2024)
The specificity of the language of Chinese media, formed under the influence of the digital environment, is considered. It has been established that modern media texts use text symbols in the form of pinyin abbreviations to make the materials more concise and understandable, and also widely use emoji and elements of Internet slang to attract the attention of an audience and increase the number of views. Such a transformation of the language of the media, on the one hand, allows young people to be involved in the process of consuming content, and on the other hand, it becomes a source of vulgarisation of vocabulary and leads to a loss of accuracy of the information being broadcast.